Metaphorical Conceptualization of ‘Happy’ in Nepali Embodied Idioms - Dahal, Binod (Journal of Kapan Multiple Campus, 2025)
The study focuses on phenomenology-based cognitive linguistics research in Nepali embodied idioms. The embodied emotional concept of Nepalese happiness is rooted in the conceptual system of Nepali speakers, which is examined and examined in consideration of the physiological state of the human body's organs to form a metaphor. The theoretical framework of this study is CMT (Conceptual Metaphor Theory), developed by George Lakoff and Mark Johnson. The embodiment hypothesis in Nepali idiomatic expression is explored in this study; however, the primary metaphors, based on the body, are likely to be universal. This study investigates the experience of spatial and substance in the body container (physical source domain) in their understanding of the abstract conceptualization of happiness (target domain). The conclusion of this investigation shows that the conceptual system of Nepali, which has eight embodied idiomatic expressions for happiness, is deeply rooted in bodily spatial experience to establish an event/spatial structure metaphor with trajectory (landmark-trajector) in collective unconsciousness. The data were collected from the academic survey reports of Nepali idioms. The happiness-related conceptual metaphor of Nepali body-part idioms and their physicality and experiential enterprise have been empirically investigated in this research.